Implementasi Pelindungan Karya Cipta Buku Berdasarkan Undang-Undang Hak Cipta: Studi Kasus Penjualan Buku Bajakan di Marketplace Shopee - Winanda, Miftah Anggun; Saidin, Saidin; Azwar, Tengku Keizerina Devi (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This research aims to understand the implementation of Law Number 28 of 2014 in addressing pirated book sales on Shopee. This study uses an empirical legal research method, adopting a virtual ethnographic approach to understand the legal behavior of internet users. The results show that the implementation of Law Number 28 of 2014 in addressing the sale of pirated books on Shopee is still not optimal, especially regarding monitoring and law enforcement. Effective law enforcement is necessary to strengthen copyright protection and restore losses that have occurred, including removing illegal content, civil lawsuits, and applying criminal fines as consequences for negligence. Therefore, it is recommended that various parties selling books on Shopee enhance their copyright protection efforts. First, Shopee should proactively improve its monitoring system to identify and remove infringing content before transactions occur. Second, Shopee sellers should ensure that their products comply with copyright requirements. Third, consumers should raise their awareness of the importance of purchasing legitimate products and support copyright protection efforts by reporting pirated books they find on the marketplace. Lastly, copyright holders are advised to actively monitor the distribution of their work and collaborate with marketplaces like Shopee to prevent copyright infringements and utilize available legal mechanisms to take action against violations. Through coordinated cooperation among all these parties, a fairer and more just environment in the digital market can be expected.